Respone of different sweet corn varieties to application of chemical fertilizer, poultry manure and Bacillus sphaericus (UPMB10) - Kamaruddin, Mohamad Hafis (2016)
The expansion of sweet corn cultivation offer an alternative option to the present pineapple cultivation on peat in Malaysia. The major sweet corn growing areas are located in Pontian, Johor (1°29'8.02" N; 103°23'16.3" E), Kuala Langat, Selangor (2°48'13.8" N; 101°29'42.3" E) and Bintulu, Sarawak (3°10'16.8" N; 113°2'30.9" E). This experiment was conducted at Integrated Peat Soil Research Station (IPRS) Pontian, Johor. The size of study plots was 1.5 m x 1.5 m and planting distance was 75 cm x 25 cm. Randomized Completely Block Design (RCBD) was used as the experimental design with four replications. All the fertilizers were applied on the first week after planting. The objectives of the first experiment was to determine the effect of Bacillus sphaericus (UPMB10), poultry manure (PM) and chemical fertilizer (CF) combinations and determine the effective rate of fertilizers on yield and quality of sweet corn grown on peat soils. The combination of UPMB10, poultry manure and chemical fertilizers were to exploit the yield potential of Hybrimas sweet corn. The treatments used were T1: No Fertilizer, T2: Chemical Fertilizer (160 kg N/ha, 34 kg P2O5/ha, 90 kg K2O/ha), T3: Poultry Manure (3.56 tonnes/ha), T4: Bacillus sphaericus (UPMB10) (50L of Solution and 10,000L of Water), T5: 50%CF + 50%PM, T6: 50%PM + 50%UPMB10, T7: 50%CF + 50%UPMB10, T8: 30%CF + 30%PM + 40%UPMB10. Treatment T6 (50% Poultry Manure + 50% UPMB10) resulted in the highest plant height at 6, 8 and 10 weeks after planting (WAP) compared to other treatments. It also gave the highest root volume of Hybrimas sweet corn (6077.5 cm3). Root and ear lengths, fresh and dry weights of ear were obtained to be the highest at T4 (UPMB10) but these parameters were not significantly different from T6. The objective of the second experiments was to determine the effect of fertilizer treatments on selected varieties of sweet corn on peat soils. The best fertilizer rate obtained from the first experiment was applied to second experiment at the first week after planting. Five varieties of sweet corn were grown on peat soil were Thai Supersweet (V1), 316 (V2), Hybrimas (V3), 1001Y (V4) and 6001BC (V5). Seed germination of Hybrimas (V3) sweet corn showed the highest percentages (97%) compared other varieties. Hybrimas sweet corn showed the highest plant height at 4 WAP, 8 WAP and 10 WAP. Root volume, root length, leaf area, ear length, total chlorophyll and soluble solid content (SSC) were highest from Hybrimas (V3). Fresh and dry weights of plant were also found to be high on 316 (V2) sweet corn at 545 g and 361.5 g respectively. Sensory evaluation showed that the Hybrimas (V3) gave highest score on appearance, sweetness, flavor and overall preference compared among varieties. A combination of 50% Poultry Manure and 50% UPMB10 (T6) was the suitable treatment for growing Hybrimas sweet corn on peat soils. Thus, Hybrimas sweet corn showed good potential for commercial production on peat soils of Peninsular Malaysia.